Patent Selections: - Bentham Science Publishers (Recent Patents on Inflammation & Allergy Drug Discovery, 2012)
The patents annotated in this section have been selected from various patent databases. These recent patents are relevant to the articles published in this journal issue, categorized by therapeutic areas/targets & therapeutic agents related to inflammation and allergy drug discovery.